THE USE OF AUDIO-LINGUAL METHOD IN LANGUAGE TEACHING AT SCHOOL (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the application of the Audio-Lingual Method (ALM) in language teaching at schools. The main focus is on the method's structure, benefits, and challenges in developing students’ speaking and listening skills. The ALM emphasizes repetitive drills and pattern practice, aiming to form correct language habits. Through this approach, students can gain fluency and accuracy in their target language, particularly in oral communication.